How to survive in the woods : a novel - Rosenfield, Kat (Harper, an imprint of HarperCollins Publishers, 2026)
"Raised by a doomsday prepper and hardened by the startup world, Emma Sharp has learned how to endure--especially in her marriage to Logan Grant, a charismatic tyrant who keeps her under tight control. To Emma, her marriage is a cage: it keeps you in, but it also keeps you safe. Until it doesn't. When Emma forms an unexpected bond with Logan's former girlfriend, the two women form a plan to help Emma take her life back. Destination: the punishing final stretch of the Appalachian Trail known as the Hundred Mile Wilderness. After all, bad things happen in the woods all the time. As the three venture deeper into Maine's backcountry, desire and dread curdle into something unpredictable, dark, and deadly. Someone is lying. Someone is watching. And in the remote heart of the forest, someone is about to be lost . . . or found"--